Confronting the Challenges in Lithium Anodes for Lithium Metal Batteries - Wang, Qingyu; Liu, Bin; Shen, Yuanhao; Wu, Jingkun; Zhao, Zequan; Zhong, Cheng; Hu, Wenbin (Advanced science, 2021)
With the low redox potential of −3.04 V (vs SHE) and ultrahigh theoretical capacity of 3862 mAh g−1, lithium metal has been considered as promising anode material. However, lithium metal battery has ever suffered a trough in the past few decades due to its safety issues. Over the years, the limited energy density of the lithium‐ion battery cannot meet the growing demands of the advanced energy storage devices. Therefore, lithium metal anodes receive renewed attention, which have the potential to achieve high‐energy batteries. In this review, the history of the lithium anode is reviewed first. Then the failure mechanism of the lithium anode is analyzed, including dendrite, dead lithium, corrosion, and volume expansion of the lithium anode. Further, the strategies to alleviate the lithium anode issues in recent years are discussed emphatically. Eventually, remaining challenges of these strategies and possible research directions of lithium‐anode modification are presented to inspire innovation of lithium anode. The improvement of lithium anodes plays a great role in developing lithium metal batteries with high energy density. With the aim of enlighting the future directions of the researches on lithium anodes, the challenges and progress in the field of lithium anodes in recent years are presented.